The View from the Traveller Site: Post-nomadic Subjects and the Material Relations of Permanent Temporary Dwelling - Anna Hoare (Opticon1826, 2014)
The Caravan Sites Act 1968 imposed a duty on local authorities in the United Kingdom to provide sites for ‘gipsies’ (sic). Contradictory aims of active repression, enforced dependency and notional integration combined in a mode of dwelling invented and controlled by the state, but increasingly promoted, transformed and privatised by Travellers themselves. In a ruling in 2004 against the United Kingdom, the European Court of Human Rights found that local authority sites were ‘homes’ under Article Eight of the European Convention on Human Rights, and tantalisingly described the UK’s Traveller population as ‘nomadic in spirit if not in actual or constant practice’ (Connors v. the United Kingdom, ECtHR 267, 2004, Press Release of the Registrar: 4). This paper explores the paradox of permanent temporariness imbedded in the relation between the UK Traveller site, the legal category of the gypsy, and the house of the post-war planning system. It argues that post-nomadic architectures and subjectivities radically challenge the public-private nexus of citizenship, property, and family objectified in the post-war ideal of the permanent house. In the house, as Engels (1948 [1891]) describes, political economy and the materiality of dwelling and family life collide, and the tension of contradictions eventually gives rise to new house forms and concomitant social relations. The paper draws on anthropological fieldwork in the UK and Ireland to revisit the house as a field of productive instability.
Keywords: gypsies; caravan sites; law; House